Breaking Male Domination In Phyllida Lloyd's Iron Lady Movie (2011) : A Feminist Perspective - Feriana, Linda; , Dra. AbdillahNugroho, M.Hum; , Titis Setyabudi, S.S, M.Hum (2013)
The study discusses about how breaking of male domination in Phyllida Lloyd Iron Lady movie (2011). The objective of the study is to analyze structural elements of this movie and breaking male domination of this movie based on the feminist perspective. On this research, the researcher applies qualitative research by using feminist approach. The object of the study is Iron Lady by PhyllidaLlyod and was produced in 2011 by Weinstein Company.The data sources consist of two parts; there are primary data sources and secondary data sources. The primary data source is Iron Lady Movie produced by Weinstein Company. The secondary data are manuscript and synopsis of Iron LadyMovie. The researcher also uses bibliography of the director of this movie as a secondary data sources. The method of collecting data usesdocumentation. In analyzing the data, the writer applies descriptive approach. The results of this study consist of two parts. First, after analyzingIron LadyMovie, the researcher shows that Phyllida Lloyd can combine the structural analysis into a good unity. Second, based on the feminist analysis of Iron Lady movie, the researcher can elaborate that Phyllida Lloyd shows that Margaret can get the position, role, right on her live. She also can participate on social and politic sphere. Phyllida Lloyd also presents that women have the same opportunities with men to get and develop their carrier.